The living condition in the historic city of Penang in Malaysia - Karim, A.H.M Zehadul; Bakar , Mohd. Isa; Chan , Hua Chiang (Serials Publications, New Delhi, 2010)
This paper on the living condition in the City Center of Southeast Asia is an analysis of the restructured way of life and living in two centrally located and historically significant streets of Penang City in Malaysia. from historical points of view, these locations represent one of the oldest settlement areas of Penang, having exposure to business privileges and commercial facilities. The study aims at understanding th better effects of housing located in these historically significant inner city centers as they undergo transformation in response to the recent urban growth and socio-economic development. The newly developed urban areas in the city had brought massive changes to its specific spatial characteristics as well as in the community life of these areas as they have now been purposefully reorganized. It has been observed that with the expansion of cities, the new generations have now the tendency to move to the new localities as they provide them with modern facilities and more suitable living environment.